Analysis Of The Contribution Of Education Based On Emotional And Spiritual Intelligence In The Digital Era In Indonesia - Retno Anggraini; Sitti Hasnah; Rinovian R; Ai Siti Nurmiati; Idris Idris (PT. Banjarese Pacific Indonesia, 2025)
This research aims to analyze the contribution of education based on emotional intelligence (EQ) and spiritual (SQ) in facing the challenges of the digital era in Indonesia. The focus of the research is to understand how an educational approach that integrates EQ and SQ can help students develop relevant skills amidst rapid technological developments and social change. The research method used was qualitative with a literature study approach. The data obtained was analyzed thematically to identify patterns and impacts of the application of EQ and SQ in the context of digital education. The research results show that EQ and SQ-based education plays an important role in forming strong and adaptive student characters in the digital era. The integration of EQ helps students manage emotions, increase empathy, and build positive social relationships, while SQ strengthens spiritual values ​​that encourage the formation of responsible and ethical attitudes. This combination not only helps students deal with digital distractions, but also improves collaboration and creativity skills. Thus, EQ and SQ-based education is considered an effective solution for creating a generation that is not only intellectually intelligent, but also has the emotional and spiritual maturity needed to compete in the digital era.